Pengaruh Pendekatan Matematika Realistik terhadap Hasil Belajar Siswa Kelas VIII-1 SMP Negeri 2 Sunggal - Surbakti, Juli Agina Br.; Hasratuddin (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2025)
This study aims to determine the effect of a realistic mathematics approach on student learning outcomes and to determine whether students' mathematics learning outcomes who are given a realistic mathematics approach achieve the minimum completeness criteria, namely 75. Learning outcomes are defined as a measure of students’ success in mastering school subject, expressed in scores obtained from test results. The study was conducted at SMP Negeri 2 Sunggal in the 2025/2026 academic year using a quasi-experimental method with a purposive sampling technique. The research sample was class VIII-1 as the experimental class, and class VIII-2 as the control class. The results showed that there was a significant increase in the learning outcomes of students in the experimental class, with an average pretest score of 39.37 and a posttest score of 79.58, in the control class the average pretest score was 40.83 and a posttest score of 72.91. Based on the results of data analysis using a one-way t-test on the difference between the two means, it is known that the null hypothesis (H0) is rejected. This means that there is a significant difference between the learning outcomes of students taught using the Realistic Mathematics Approach and conventional learning. The mathematical learning outcomes of students taught using the Realistic Mathematics Approach are better than those taught using conventional learning. The results of this study show that the percentage of classical graduation of students who achieved a minimum completeness criterion score of 75 who were treated with the Realistic Mathematics Approach was 80% and the percentage of classical graduation of students who achieved a minimum completeness criterion score of 75 who were treated with conventional learning was 53.3%. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh pendekatan matematika realistik terhadap hasil belajar siswa dan untuk mengetahui hasil belajar matematika siswa yang diberi pendekatan matematika realistik mencapai kriteria ketuntasan minimal yakni 75. Hasil belajar adalah ukuran tingkat keberhasilan siswa dalam mempelajari materi pembelajaran di sekolah yang dinyatakan dalam skor yang diperoleh dari hasil tes. Penelitian dilaksanakan di SMP Negeri 2 Sunggal pada tahun ajaran 2025/2026 dengan metode quasi eksperimen dengan teknik pengambilan sampel adalah teknik purposive sampling. Sampel penelitiannya adalah kelas VIII-1 sebagai kelas eksperimen, dan kelas VIII-2 sebagai kelas kontrol. Hasil penelitian menunjukkan bahwa terdapat peningkatan yang signifikan pada hasil belajar siswa kelas eksperimen, dengan rata-rata skor pretest 39,37 dan skor posttes 79,58, pada kelas kontrol rata-rata skor pretest 40,83 dan posttest 72,91. Berdasarkan hasil analisis data menggunakan uji-t satu arah terhadap perbedaan dua rata-rata, diketahui bahwa hipotesis nol (H0) ditolak. Artinya terdapat perbedaan yang signifikansi antara hasil belajar siswa yang diajar menggunakan Pendekatan Matematika Realistik dengan pembelajaran biasa. Hasil belajar matematis siswa yang diajar menggunakan Pendekatan Matematika Realistik lebih baik dibandingkan siswa yang diajar dengan pembelajaran biasa. Hasil penelitian ini menunjukkan persentase kelulusan klasikal siswa yang mencapai nilai kriteria ketuntasan minimal 75 yang diberi perlakuan dengan Pendekatan Matematika Realistik adalah sebesar 80% dan persentase kelulusan klasikal siswa yang mencapai nilai kriteria ketuntasan minimal yang diberi perlakuan dengan pembelajaran biasa adalah sebesar 53,3%.